РОЗРОБКА ІНСТРУМЕНТАЛЬНОГО МЕТОДУ ДОСЛІДЖЕННЯ ФАКТУРИ ТКАНИНИ (World Science, 2020)
Modern consumers attach increasing importance to tactile sensations and the general perception of the surface of fabrics, therefore, the study of the structure and properties of woven textures is an urgent task of textile production. In textile technologies, organoleptic research methods are used mainly, which give a subjective visual and tactile assessment of the surface of the tissues. Therefore, there was a need to develop an instrumental method for determining the texture of fabrics, which was implemented on the basis of the existing method for studying the texture of hard surfaces. It is based on the idea of creating a constant mode of illumination of the object of observation, which is a tissue sample. The proposed method is based on the use of a special optical device for determining the qualitative and quantitative characteristics of textures and is a viewing chamber containing a mechanism for changing the lighting mode and a mechanism for capturing tissue images. For an objective assessment of the state of the surface of the tissues, the invoice indicator is calculated − the invoice coefficient. The implementation of the developed method allows to increase the efficiency of the processes of design-design of fabrics, to predict the appearance of fabrics and to ensure compliance with the texture of the fabric of the model of the garment.